THE ROLE OF TECHNOLOGY IN PROMOTING THE PRINCIPLE OF EQUALITY AT PT KOTAMAS MAKMUR NATIONAL AGENCY - Febriyanti, Ayunda; Mulalinda, Ananda Yosefa Nauli; Ahmad, Daffa Syuja; Ayyun, Dinda Ramadhani Qurrota; Herliana, Mavalda; Febriantina, Susan; Atmadja, Ferry Setyadi (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study aims to explore the role of technology in promoting the implementation of equality principles at PT. Kotamas Makmur National Agency, a company engaged in tableware and kitchenware. By utilizing a review of recent literature and interviews with management, the research identifies how technology supports the implementation of equality in human resource management, including recruitment, career development, and performance evaluation. The findings reveal that the use of technology, such as data-driven recruitment platforms and automated performance assessment systems, plays a significant role in reducing bias, increasing transparency, and ensuring fair treatment for all employees. In addition to enhancing employee satisfaction and retention, the integration of technology also fosters innovation and efficiency in the workplace. This article provides strategic recommendations for optimizing technology to reinforce equality principles, which can serve as a reference for other companies in creating inclusive and progressive work environments.